Pembuatan Formulasi Pakan Ikan dengan Penambahan Tepung Maggot BSF (Hermentia Illucens L) dan Ekstrak Daun Apu-Apu (Pistia Stratiotes L) - Syafrina Lamin; Juswardi Juswardi; Muharni Muharni; Nita Aminasih; Miksusanti Miksusanti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Efforts to increase fish farming productivity, motivating farmers to enhance the fish farming population in Pulau Semambu Village. Inderalaya Utara Village, Ogan Ilir, can be implemented through village lecture provision, training, and demonstration of artificial feed production based on maggots with the addition of water spinach leaf extract. The objective of this activity is to enhance the growth and immune system of fish livestock.Based on that reasoning, the framework of thought that will be pursued through the model approach (1) The approach is carried out through direct observation of the community while simultaneously mapping the latest fish farms in Pulau Semambu Village, Inderalaya Utara, Ogan Ilir.(2) Assistance, this activity is carried out through village lectures that can be realized in the form of outreach to fish farmers about improving fish farming management and providing support in motivating fish farmers to start implementing the concept of an intensive maintenance system in fish farming in maintenance ponds that meet health standards. (3) Direct demonstration (practice) of making artificial feed based on BSF maggots, which includes how to make water spinach leaf extract, how to maintain maggots, and how to make flour and pellets for artificial feed. The village lecture activity was attended by 40 women in the fish farming group in Pulau Semambu Village and students taking the Entomology and Entrepreneurship courses.The result of the activity is to increase the productivity and population of fish livestock in Pulau Semambu. The provision of fish feed based on a mixture of maggot flour and water spinach extract can enhance the growth and immune system of fish livestock, resulting in heavier fish that are less prone to disease. Increasing the production and population of fish livestock will result in higher incomes for the fish farmers in Pulau Semambu village, Inderalaya Utara, Ogan Ilir.